METHODS OF TRANSLATING PHRASEOLOGICAL UNITS FROM ENGLISH TO UZBEK LANGUAGE IN LITERARY TEXT - Palvannazirova Zilola Mansurbek qizi (International Journal of Literature and Language Studies, 2026)
Phraseological units constitute one of the most culturally marked and semantically complex layers of language. Their figurative nature, structural stability, and national specificity create considerable challenges in the process of translation. The present study examines the principal methods employed in translating phraseological units from English into Uzbek, focusing on semantic equivalence, descriptive rendering, calque translation, and cultural substitution. The research applies comparative and descriptive analytical methods to evaluate the effectiveness of various translation strategies in preserving meaning, stylistic coloring, and pragmatic impact. The findings reveal that equivalent translation ensures the highest degree of semantic and stylistic adequacy when corresponding idiomatic expressions exist in the target language. However, in the absence of direct equivalents, translators frequently resort to descriptive or adaptive strategies in order to maintain communicative functionality. The study emphasizes the significance of intercultural competence and contextual interpretation in phraseological translation.